Beyond Textual Traditions: The Phenomenology of Ecotheological Value Integration in Pesantren Minhajul Haq - Prima, Cahyudi; Abdurahman, Isrun; Jafar, Akhmad (Islam Futura, 2026)
This study aims to explore the lived experiences of integrating ecotheological values within traditional Islamic educational institutions. Specifically, it investigates how students at the Minhajul Haq Islamic Boarding School in Indonesia transition from theoretical environmental jurisprudence to practical ecological spirituality through daily conventional agriculture and modern hydroponic activities. Employing a qualitative Husserlian phenomenological approach, this research systematically examines the students' lived experiences. Following a preliminary screening to purposively identify key informants, primary data collection combined semi-structured interviews, direct participant observations, macro-spatial aerial drone photography, and the visual documentation of micro-activities. Data analysis was conducted using a thematic coding approach assisted by NVivo 12 software. The findings reveal a paradigm shift towards applied ecotheology. Students are directly exposed to ecological management, where macro-spatial green design integrates seamlessly with micro-agricultural activities, facilitating the development of a holistic eco-spiritual identity that extends beyond traditional textual memorization. This research provides an actionable framework for the disciplines of the sociology of religion, environmental ethics, and Islamic educational management. Furthermore, the findings offer empirical insights for education policymakers and institutional administrators seeking to design and implement sustainable experiential learning models in religious boarding schools. By combining spatial visual data with micro-level phenomenological experiences, this study contributes to the contemporary discourse on Islamic environmental education, advancing beyond purely normative theological narratives.